The chromium isotope composition of reducing and oxic marine sediments. (1st July 2016) - Gueguen, Bleuenn; Reinhard, Christopher T.; Algeo, Thomas J.; Peterson, Larry C.; Nielsen, Sune G.; Wang, Xiangli; Rowe, Harry; Planavsky, Noah J.
Abstract: The chromium (Cr) isotope composition of marine sediments has the potential to provide new insights into the evolution of Earth-surface redox conditions. There are significant but poorly constrained isotope fractionations associated with oxidative subaerial weathering and riverine transport, the major source of seawater Cr, and with partial Cr reduction during burial in marine sediments, the major sink for seawater Cr. A more comprehensive understanding of these processes is needed to establish global Cr isotope mass balance and to gauge the utility of Cr isotopes as a paleoredox proxy. For these purposes, we investigated the Cr isotope composition of reducing sediments from the upwelling zone of the Peru Margin and the deep Cariaco Basin. Chromium is present in marine sediments in both detrital and authigenic phases, and to estimate the isotopic composition of the authigenic fraction, we measured δ 53 Cr on a weakly acid-leached fraction in addition to the bulk sediment. In an effort to examine potential variability in the Cr isotope composition of the detrital fraction, we also measured δ 53 Cr on a variety of oxic marine sediments that contain minimal authigenic Cr. The average δ 53 Cr value of the oxic sediments examined here is −0.05 ± 0.10‰ (2 σ, n = 25), which is within the range of δ 53 Cr values characteristic of the bulk silicate Earth. This implies that uncertainty in estimates of authigenic δ 53 Cr values based on bulk sediment analyses is mainly linked to estimation of the ratio of Cr in detrital versus authigenic phases, rather than to the Cr-isotopic composition of the detrital pool. Leaches of Cariaco Basin sediments have an average δ 53 Cr value of +0.38 ± 0.10‰ (2 σ, n = 7), which shows no dependency on sample location within the basin and is close to that of Atlantic deepwater Cr (∼+0.5‰). This suggests that authigenic Cr in anoxic sediments may reliably reflect the first-order Cr isotope composition of deepwaters. For Peru Margin samples, the average δ 53 Cr values of bulk sediments (+0.59 ± 0.06‰; 2 σ ) and leach fractions (+0.61 ± 0.06‰; 2 σ ) are also comparable with those of Cariaco Basin samples and modern deepwater values. Finally, we found that the δ 53 Cr of Peru Margin samples correlates with δ 15 N on glacial–interglacial timescales, which we attribute to secular variation in basinal or global-ocean redox conditions. Thus, the δ 53 Cr stratigraphic record of Peru Margin sediments indicates that Cr isotopes may be suited to tracking geologically short-term changes in ocean oxygenation.